Hepatitis C Testing Increased Among Baby Boomers Following The 2012 Change To CDC Testing Recommendations - Barocas, Joshua A. (Health Aff (Millwood), 2017)
In 2012 the Centers for Disease Control and Prevention recommended routine testing for hepatitis C for people born in the period 1945–65. Until now, the recommendation’s impact on hepatitis C screening rates in the United States has not been fully understood. We used an interrupted time series with comparison group design to analyze hepatitis C screening rates in the period 2010–14 among 2.8 million commercially insured adults in the MarketScan database. Hepatitis C screening rates increased yearly between 2010 and 2014, from 1.65 to 2.59 per 100 person-years. A 49 percent increase in screening rates among people born during 1945–65 followed the release of the recommendation, but no such increase was observed among adults born after 1965. The effect among the target population was sustained, and by twenty-four months after the recommendation’s release, screening rates had increased 106 percent. We conclude that the hepatitis C testing policy change resulted in significantly increased testing among the target population and may have decreased the magnitude of the hepatitis C epidemic.